Features of atmospheric pressure discharges with a transverse component of the velocity of gas flow to the current channel - Chernyak, V.Ya.; Iukhymenko, V.V.; Iukhymenko, K.V.; Klochok, N.V.; Kolomiiets, O.V.; Hamazin, D.K.; Chernolutsky, D.L. (Вопросы атомной науки и техники, 2018)
The atmospheric pressure rotating gliding discharge was studied in work. A comparison of a rotating gliding
discharge with a discharge in a transverse airflow were made. The clear analogies between rotating gliding
discharge and discharge in the transverse airflow, were found during research. Досліджувався обертовий ковзний розряд атмосферного тиску. Було проведено порівняння обертового
ковзного розряду з розрядом у поперечному потоці повітря. У ході проведених досліджень обертового
ковзного розряду та розряду в поперечному потоці повітря були виявлені чіткі аналогії між цими розрядами. Исследовался вращающийся скользящий разряд атмосферного давления. Было проведено сравнение
вращающегося скользящего разряда с разрядом в поперечном потоке воздуха. В ходе проведенных
исследований вращающегося скользящего разряда и разряда в поперечном потоке воздуха были выявлены
четкие аналогии между этими разрядами.